If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -6y = 19 Solving 11x + -6y = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 11x + -6y + 6y = 19 + 6y Combine like terms: -6y + 6y = 0 11x + 0 = 19 + 6y 11x = 19 + 6y Divide each side by '11'. x = 1.727272727 + 0.5454545455y Simplifying x = 1.727272727 + 0.5454545455y
| (u-4)*10=20 | | (e+3)*5=25 | | 2y-3=4y-1 | | 5x+2=-2x+9 | | -6(w+5)=6 | | (q-7)*2=12 | | 4-m/-5=18 | | 23-(44*x)=199 | | 3n^3-5n^2=0 | | (e+1)*2=10 | | 9z+20=2 | | 34*26x=18 | | 3(t+5)=9 | | -20(-5k-8)=-40 | | (u-6)*8=32 | | 72−x/2=-88 | | A-3x=XA+B | | -56+8x=200 | | -16*-2=32 | | (2x)/.5=10x-21 | | y=2e^3x+1 | | 6(y+2)+3(2y-3)=#( | | P^14=0.01 | | 1x-15= | | 8x+4=24x-8 | | a^2-2a-35=o | | 23-(44-x)=199 | | 12039532+2045=x | | 4+3p= | | 18-4x=6-8x | | 8s^2+18s-35=0 | | 7/10*1/3*2/21 |